Cardiac events and dynamic echocardiographic and electrocardiogram changes following osimertinib treatment in lung cancer - Le, Jonathan N.; Gasho, Jordan O.; Peony, Olivia; Singh, Asneh; Silos, Katrina D.; Kim, Sungjin; Nguyen, Anthony T.; Kamrava, Mitchell; Mirhadi, Amin; Hakimian, Behrooz; Reckamp, Karen L.; Sankar, Kamya; et al. (Frontiers in Cardiovascular Medicine, 2024)
Osimertinib is first-line treatment for epidermal growth factor (EGFR)-mutated non-small cell lung cancer (NSCLC) and has been associated with cardiotoxicity. However, the nature of cardiac remodeling and associated risk factors remains incompletely understood. Retrospective analysis of NSCLC patients with ≥1 echocardiogram post-osimertinib between 2007 and 2022 was performed. The cumulative incidence of grade ≥2 cardiac common terminology criteria for adverse events (CTCAE) was estimated and Fine and Gray regressions performed (non-cardiac death as competing risk). Eighty-five patients [mean [interquartile range, IQR], 68 [60–75] years; 67% female; 12% with pre-existing heart conditions] met inclusion criteria. With a median follow up of 34.7 months, the 2-year cumulative incidence of grade ≥2 and grade ≥3 cardiac events were 19.2% and 8.5%, respectively. There was an increased risk of grade ≥2 cardiac CTCAE with pre-existing arrhythmia [hazard ratio(HR) 3.90, 95%CI, 1.11–13.72; p = 0.034] and higher body mass index (HR 1.07, 95%CI, 1.00–1.14; p = 0.04). Following osimertinib (vs. baseline), the median QTc was prolonged (451 vs. 437 ms; p < 0.001) and LVEF ≤50% was more common (10.6% vs. 5.3%; p = .046). Osimertinib treatment was associated with QTc prolongation and reduced LVEF. BMI was identified as a potentially modifiable risk factor for osimertinib-associated cardiotoxicity, worthy of further study.